Perancangan Buku Fotografi Story Deskriptif Seni dan Budaya Sumba Timur Sebagai Upaya Pengenalan Kesenian dan Kebuyaan Suku Sumba. - Hastadewa, Gusti; Martono, Siswo; Hidayat, Wahyu (Jurnal Art Nouveau, 2018)
Indonesia is an country that has 17,504 islands, from these islands Indonesia has many diversitiessuch as ethnicity, culture, and religion. Currently there are many arts and cultures along withethnic groups in Indonesia that are not yet known by the public. One of them is the Sumba tribelocated in the Sumba island, East Nusa Tenggara. Sumba Island has indigenous tribes Sumbatribes located in several places in West and East Sumba, East Sumba has several tribes such asLewa, Pariawang, and Rindi. The tribes are scattered in several places such as lewa, karera, andpariawang. They had a lot of culture such as dance, ikat weave, and music.